2020
DOI: 10.3389/fmicb.2020.01309
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Hypervirulent Serovar 4h Listeria monocytogenes by Multiplex PCR

Abstract: Listeria monocytogenes (L. monocytogenes) is a ubiquitous foodborne pathogen that comprises 14 serotypes, of which serovar 4h is a novel serotype recently reported. Serovar 4h L. monocytogenes belonging to hybrid sub-lineage II exhibit hypervirulent features. Conventional biochemical tests and widely used PCR-based serogrouping schemes could not distinguish serovar 4h strains. In this study, we developed a new multiplex PCR assay for rapid detection of serotype 4h L. monocytogenes. Three primer pairs based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…L. monocytogenes is a heterogenous group of bacteria. This bacterium can be differentiated into 14 different serotypes, with serovar 4 h being recently described [ 16 , 17 ]. These serotypes are divided into four lineages (denoted as I-IV) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes is a heterogenous group of bacteria. This bacterium can be differentiated into 14 different serotypes, with serovar 4 h being recently described [ 16 , 17 ]. These serotypes are divided into four lineages (denoted as I-IV) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the genetically heterogeneous nature of L. monocytogenes, serotyping as the primary characterization in epidemiological surveillance has been widely accepted [46]. Feng et al [47] developed a new multiplex PCR assay for rapid detection of new serotype 4h L. monocytogenes. These results demonstrate that the multiplex PCR with high specificity and sensitivity is applicable for the rapid detection of L. monocytogenes serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It encompasses the smcL gene coding for sphingomyelinase (involved in phagosome disruption) and 10 genes coding for proteins of the internalin family ( Domínguez-Bernal et al, 2006 ). However, recent studies showed that L. monocytogenes isolates, belonging to a new sub-lineage of the major lineage II with hypervirulent features (SL626/CC33, serovar 4 h), contain a truncated LIPI-2, i.e., carrying only smcL and two internalins genes, namely i-inlF and i-inlE , likely acquired by transposon-mediated horizontal gene transfer from L. ivanovii ( Yin et al, 2019 ; Feng et al, 2020 ).…”
Section: Listeria Monocytogenes Diversity and Heterogeneity ...mentioning
confidence: 99%